Satellite telemetry reveals population specific winter ranges of beluga whales in the Bering Sea. Issue 1 (14th September 2016) - Citta, John J.; Richard, Pierre; Lowry, Lloyd F.; O'Corry‐Crowe, Gregory; Marcoux, Marianne; Suydam, Robert; Quakenbush, Lori T.; Hobbs, Roderick C.; Litovka, Denis I.; Frost, Kathryn J.; Gray, Tom; Orr, Jack; et al.
Abstract: At least five populations (stocks) of beluga whales ( Delphinapterus leucas ) are thought to winter in the Being Sea, including the Bristol Bay, Eastern Bering Sea (Norton Sound), Anadyr, Eastern Chukchi Sea, and Eastern Beaufort Sea (Mackenzie) populations. Belugas from each population have been tagged with satellite‐linked transmitters, allowing us to describe their winter (January–March) distribution. The objectives of this paper were to determine: (1) If each population winters in the Bering Sea, and if so, where? (2) Do populations return to the same area each year ( i.e ., are wintering areas traditional)? (3) To what extent do the winter ranges of different populations overlap? Tagged belugas from all five populations either remained in, or moved into, the Bering Sea and spent the winter there. Each population wintered in a different part of the Bering Sea and populations with multiple years of data (four of five) returned to the same regions in multiple years. When data were available from two populations that overlapped in the same year, they did not occupy the shared area at the same time. Although our sample sizes were small, the evidence suggests belugas from different populations have traditional winter ranges that are mostly exclusive to each population.